Storage networking fundamentals : an introduction to storage devices, subsystems, applications, management, and filling systems. - Farley, Marc, ....- (Indianapolis : Cisco, 2005)
Part I The Big Picture of Storage Networking Chapter 1 Data Access in the Internet Era Chapter 2 Establishing a Context for Understanding Storage Networks Chapter 3 Getting Down with Storage I/O Part II Working with Devices and Subsystems in Storage Networks Chapter 4 Storage Devices Chapter 5 Storage Subsystems Chapter 6 SCSI Storage Fundamentals and SAN Adapters Chapter 7 Device Interconnect Technologies for Storage Networks Part III Applications for Data Redundancy Chapter 8 An Introduction to Data Redundancy and Mirroring Chapter 9 Bigger, Faster, More Reliable Storage with RAID Chapter 10 Redundancy Over Distance with Remote Copy Chapter 11 Connection Redundancy in Storage Networks and Dynamic Multipathing Part IV The Foundations of Storage and Data Management Chapter 12 Storage Virtualization- The Power in Volume Management Software and SAN Virtualization Systems Chapter 13 Network Backup- The Foundation of Storage Management Part V Filing Systems and Data Management in Networks Chapter 14 File System Fundamentals Chapter 15 Network File Systems and Network Attached Storage Chapter 16 New Directions in Network Filing- Clustered File Systems, Distributed File Systems, and Network Storage for Databases Chapter 17 Data Management Part VI Appendixes Appendix A Q & A Answers Appendix B INCITS Storage Standards Glossary Index
Keywords: Computernetwerken